Analisis Persepsi Guru dan Siswa dalam Pembelajaran Biologi pada Penerapan Kurikulum Merdeka - widya eko nurazizah; Diana Rochintaniawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Education has an important role in developing individual potential and dealing with changes in science and technology. Biology learning involves complex abstract concepts and scientific facts, so that students experience difficulties in learning them. Learning problems can come from various sources such as students, teachers, books or media, and curriculum. The independent curriculum, which was introduced in the 2021/2022 academic year, requires students to have the ability to create solutions to problems based on local, national or global issues, as well as actively participate in achieving sustainable development goals. The new curriculum also has the potential to cause problems in learning. In this context, an analysis needs to be carried out to understand how biology is taught in the implementation of an independent curriculum. This study was conducted through observation of teachers and class X students at a high school in Bandung. Data was collected through interviews and questionnaires to teachers and students. The data obtained were analyzed descriptively. The results of initial observations indicate that there are obstacles in the implementation of the independent curriculum, especially in the P5 project with the theme of diversity. Follow-up observations in this study focused on the analysis of biology learning in the independent curriculum. The findings show that students' interest and enthusiasm in learning biology is high, although the level of student mastery needs to be improved. The PjBL concept and model approach is the teacher's main preference, even though there are time constraints and project coordination outside of class hours. The use of technology is not optimal even though LMS and interactive multimedia are available. The implementation of the independent curriculum was good, but there were obstacles to learning outcomes, inefficient time allocation, and difficulties in working on projects. It is recommended to increase student completeness, maximize the use of technology, vary approaches, and improve the implementation of the independent curriculum with more specific goals and efficient time.